Safety and efficacy of brentuximab vedotin in patients with Hodgkin lymphoma or systemic anaplastic large cell lymphoma - Vaklavas, Christos (SAGE Publications, 2012)
Antibody-based immunotherapy has become an integral part of cancer therapeutics. However, monoclonal antibodies have their limitations as identifying an antigen selectively expressed on malignant cells and developing a high-affinity antibody may not by itself alter tumor growth. This is illustrated in the case of CD30; CD30 epitomizes many properties of an ideal pharmacologic target such as high expression on malignant cells and limited expression on normal tissues. However, until the advent of brentuximab vedotin, CD30 remained an elusive target as antibody-based anti-CD30 immunotherapy had been largely clinically unsuccessful. Brentuximab vedotin (cAC10-vcMMAE, SGN-35) is an antibody-drug conjugate consisting of a chimeric anti-CD30 monoclonal antibody whereupon the potent microtubule inhibitor monomethyl auristatin E (MMAE) is attached via a valine–citrulline linker. Once bound to CD30, brentuximab vedotin is internalized and MMAE is released with the action of lysosomal enzymes on the linker. In phase I studies in relapsed or refractory Hodgkin lymphoma and anaplastic large cell lymphoma, brentuximab vedotin induced unprecedented responses with manageable toxicity. In phase II studies, brentuximab vedotin induced overall response rates of 75% and 86% in relapsed or refractory Hodgkin lymphoma and anaplastic large cell lymphoma, respectively. The results of these trials led to the accelerated approval of the drug by the US Food and Drug Administration in a patient population with few other alternative options. Brentuximab vedotin has overall manageable toxicity profile; however, cumulative peripheral neuropathy constitutes an important clinical consideration as it may limit prolonged administration of the drug. The mechanism by which brentuximab vedotin exerts its antitumor activity is not entirely clear. Diffusion of MMAE in the tumor microenvironment and cytotoxicity on bystander cells may in part explain its activity, especially in Hodgkin lymphoma. Herein, we review the biology of CD30 and brentuximab vedotin, and the clinical data that has accumulated thus far with SGN-35.